The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.2147/ijgm.s351342
|View full text |Cite
|
Sign up to set email alerts
|

Lower Plasma Albumin, Higher White Blood Cell Count and High-Sensitivity C-Reactive Protein are Associated with Femoral Artery Intima-Media Thickness Among Newly Diagnosed Patients with Type 2 Diabetes Mellitus

Abstract: Introduction Low albumin levels, high levels of high-sensitivity C-reactive protein (hs-CRP), and high white blood cell count were risk factors for changes in arterial intima-media thickness (IMT). Femoral artery IMT damages were one of the common peripheral artery type 2 diabetes. This study was conducted to determine the association between femoral artery IMT and plasma albumin, hs-CRP levels, and white blood cell count in newly diagnosed patients with type 2 diabetes mellitus (nT2D). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 63 publications
(58 reference statements)
0
1
0
Order By: Relevance
“…The correlation between A. carotid KIM values and fGLP-1 serum levels in this study was analyzed using the Spearman correlation test (Phi Thi Nguyen et al, 2022). From the results of the analysis, it was found that the KIM A. carotid value and fGLP-1 serum levels had a negative correlation, with a strong correlation strength, which was expressed by the value of r = -0.748 and the degree of significance of p = 0.000.…”
Section: Correlation Of Carotid Artery Intima Media (Kim) Thickness W...mentioning
confidence: 70%
“…The correlation between A. carotid KIM values and fGLP-1 serum levels in this study was analyzed using the Spearman correlation test (Phi Thi Nguyen et al, 2022). From the results of the analysis, it was found that the KIM A. carotid value and fGLP-1 serum levels had a negative correlation, with a strong correlation strength, which was expressed by the value of r = -0.748 and the degree of significance of p = 0.000.…”
Section: Correlation Of Carotid Artery Intima Media (Kim) Thickness W...mentioning
confidence: 70%
“…Functioning as a po antioxidant, albumin aids in neutralizing free radicals-unstable molecules respon for cellular damage and heightened cancer risk [29]. Furthermore, albumin plays a piv role in immune system functionality, safeguarding against endothelial dysfunc through immunomodulation and antioxidant mechanisms [56]. Diminished albu levels could potentially trigger inflammation and an increase in leukocyte count [57 a significant source of amino acids, albumin contributes to essential protein synth required for healthy cell growth and division; deficiencies in this synthesis have correlated with an elevated cancer risk [58,59].…”
Section: Albumins Of Flaxseedmentioning
confidence: 99%
“…Functioning as a potent antioxidant, albumin aids in neutralizing free radicals-unstable molecules responsible for cellular damage and heightened cancer risk [29]. Furthermore, albumin plays a pivotal role in immune system functionality, safeguarding against endothelial dysfunction through immunomodulation and antioxidant mechanisms [56]. Diminished albumin levels could potentially trigger inflammation and an increase in leukocyte count [57].…”
Section: Albumins Of Flaxseedmentioning
confidence: 99%
“…Functioning as a potent antioxidant, albumin aids in neutralizing free radicals-unstable molecules responsible for cellular damage and heightened cancer risk [19]. Furthermore, albumin plays a pivotal role in immune system functionality, safeguarding against endothelial dysfunction through immunomodulation and antioxidant mechanisms [47]. Diminished albumin levels could potentially trigger inflammation and an increase in leukocyte count [48].…”
Section: Albumins Of Flaxseedmentioning
confidence: 99%